Effect of selenium on heavy metal bioaccumulation and antioxidant responses in black gram and rice seedlings under cadmium and lead stress: A comparative study: Selenium effects on Cd and Pb stress in black gram and rice - Samal, Nibedita; Das, Manoja; Behera, Kambaska Kumar (ORYZA-An International Journal of Rice, 2025)
Heavy metal stress from cadmium (Cd) and lead (Pb) is a major constraint on crop productivity, impairing biomass accumulation and inducing oxidative damage. This study investigates the comparative impact of Cd and Pb toxicity on black gram (Vigna mungo (L.) Hepper, cv. Ujala) and rice (Oryza sativa cv. Arnapurna) seedlings, with a focus on selenium (Se) supplementation as a mitigating agent. Results demonstrated that both metals significantly reduced biomass, particularly in roots up to 55.22% in rice and 60% in black gram, under Pb stress. Co-application of Se alleviated metal-induced growth inhibition, improving shoot biomass by up to 18.15%, 9.34% and root biomass by up to 31.11%, 20.89% respectively in black gram followed by rice. Metal accumulation was higher in roots than in shoots, but Se co-treatment significantly reduced Cd and Pb uptake, reflected in lowered Bioconcentration Factor (BCF) values. Enhanced Translocation Factor (TAR), Translocation Index (Ti), and Tolerance Index (TI) under Se treatment indicated improved metal translocation and physiological tolerance. Additionally, Cd and Pb stress elevated activities of antioxidant enzymes, peroxidase (POX), catalase (CAT), and superoxide dismutase (SOD) by more than two-fold, particularly in shoot tissues. Se supplementation further amplified antioxidant enzyme activities (up to 3-fold), suggesting enhanced reactive oxygen species (ROS) scavenging and reduced oxidative stress. These findings highlight selenium's potential as an effective ameliorant for Cd and Pb toxicity in black gram and rice by reducing metal uptake, improving stress tolerance, and enhancing antioxidative defense mechanisms.